Epinephrine but not vasopressin attenuates the airway response to anaphylactic shock in rats. (16th March 2017) - Zheng, Feng; Copotoiu, Ruxandra; Tacquard, Charles; Demoulin, Bruno; Malinovsky, Jean Marc; Levy, Bruno; Longrois, Dan; Barthel, Grégoire; Mertes, Paul Michel; Marchal, François; Demoulin-Alexikova, Silvia; Collange, Olivier
ABSTRACT: Purpose : The two life-threatening signs of anaphylactic shock (AS) are severe arterial hypotension and bronchospasm. Guidelines recommend epinephrine as first-line treatment. Arginine vasopressin (AVP) has been proposed as an alternative if epinephrine does not correct arterial hypotension. These two drugs may have beneficial, neutral or deleterious effects on airflow either directly or by modifying factors that regulate vasodilatation and/or edema in the bronchial wall.Aim of the Study : To compare the effects of epinephrine and AVP on airflow and airway leakage in a rat model of AS.Materials and Methods : Thirty-two ovalbumin-sensitized rats were randomized into four groups: control (CON), AS without treatment (OVA), AS treated with epinephrine (EPI), and AS treated with AVP (AVP). Mean arterial pressure (MAP), respiratory resistance and elastance and microvascular leakage in the airways were measured.Results: All OVA rats died within 20 minutes following ovalbumin injection. Ovalbumin induced severe arterial hypotension and airway obstruction (221 ± 36 hPa.s.L −1 vs. vehicle 52 ± 8 hPa.s.L −1 ; p < 0.0001) associated with microvascular leakage distributed throughout the trachea, bronchi and intra-pulmonary airways. EPI and AVP extended survival time; EPI restored a higher level of MAP than AVP. Airway obstruction was attenuated by epinephrine (146 ± 19 hPa.s.L −1 ; p < 0.0001), but not by AVP (235 ± 58 hPa.s.L −1 ; p = 0.42).Conclusions : Epinephrine was superior to AVP for alleviating the airway response in a rat model of AS. When bronchospasm and severe arterial hypotension are present during AS, epinephrine should be the drug of choice.